Progress in combating antibiotic resistance in animal agriculture - Tianming Xu; Jing Liu; Qian Wu; Xiaoran Hui; Weidan Duan; Zhaohuan Zhang; Xinyu Liao; Yong Zhao (CyTA - Journal of Food)
Antibiotics are commonly used to address animal health issues and enhance overall productivity in animal agriculture. However, overuse and misuse of antibiotics has become a concern in the field of agriculture and pose potential food safety risks. Efficiently controlling antibiotic resistance in animal agriculture is of vital importance. Various technologies have been developed and employed to prevent and control antibiotic-resistant bacteria in this field, such as ozone sterilization technology, among others. This review provides a comprehensive overview of current sterilization technologies in animal agriculture, including chemical sanitizers, plasma oxidation, bacteriophage, ozone, ultraviolet, ultrasonic irradiation, and photodynamic inactivation. Furthermore, we present novel insights and future perspectives on the prevention and control of antibiotic resistance in animal agriculture.